2010
DOI: 10.1002/jmri.22134
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional transcatheter intra‐arterial perfusion MR imaging before and after uterine artery embolization in the rabbit VX2 tumor model

Abstract: Purpose: To test the hypothesis that four-dimensional (4D) transcatheter intra-arterial perfusion (TRIP) MR imaging can measure uterine fibroid perfusion changes immediately before and after uterine artery embolization (UAE) in the rabbit VX2 tumor model. Materials and Methods:Eight VX2 uterine tumors were grown in six rabbits. After positioning a catheter within the uterine artery, we performed 4D TRIP-MRI measurements with 3-mL injections of 2.5% gadopentetate dimeglumine. We used a dynamic 3D spoiled-gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…DSA imaging was used smoothly in above rabbit uterine tumor model as a functional imagery way to obtain blood perfusion by a mask subtraction method. The imaging obtained before urografin given was used to produce a mask, which was subtracted [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…DSA imaging was used smoothly in above rabbit uterine tumor model as a functional imagery way to obtain blood perfusion by a mask subtraction method. The imaging obtained before urografin given was used to produce a mask, which was subtracted [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embolization follow up showed that the procedure was successful when fibroids were unenhanced and the uterine arteries were invisible on perfusion MRI [27] . In a rabbit tumor model, Chung et al [28] used intra-arterial bolus injection of gadoliniumbased MR contrast medium to measure uterine fibroid perfusion before and after uterine artery embolization. After positioning a catheter within the uterine artery and injecting the microemboli, they found that uterine tumor perfusion decreased by 76% on MRI.…”
Section: Body Interventionsmentioning
confidence: 99%